Höchste Zeit für einen Gaspreisdeckel: ein wichtiges Instrument im Kampf gegen Energiepreisbelastung; High time for a gas price cap: An important instrument in the fight against energy price burdens - Sebastian Dullien; Isabella M. Weber (Wirtschaftsdienst, 2022)
– The explosive increase of the price of natural gas is a key driver of inflation in Germany. At the same time, physical gas shortages in the fall or winter are a plausible scenario. A policy response is urgently needed that protects households from skyrocketing heating costs while at the same time maintaining price incentives to save gas. We have proposed a gas price cap for households' basic consumption and market prices for all demand above that guaranteed base. Our proposal has been widely discussed by economists and policy makers. In this article, we respond to some criticisms, provide details on the feasibility of our proposal, and urge for swift political action.
Keywords: D47; E31; H12; P18; 330; Erdgas; Energiepreis; Deutschland